Philosophy of Liberation and epistemology: contributions to critical social sciences: Philosophy of Liberation and epistemology: contributions to critical social sciences - RETAMOZO, Martín (Utopía y Praxis Latinoamericana, 2022)
Philosophy of liberation has aimed to build critical knowledge from the situation in Latin America. However, there have been considerably fewer efforts to epistemologically and methodologically ground a critical social science from this perspective. This article seeks to contribute to this question. Based on a study of Enrique Dussel's contributions, it proposes to distinguish the  method as a theoretical rupture and as a methodological proposal. The treatment of these issues raises a set of crucial problems for the foundation of a critical social science program.